A case of vaginal varicosities without rupture after vaginal delivery - Tandiono, Eunike Jennifer; Aryasatiani, Ekarini; Santoso, Brigita Naomi (Universitas Airlangga, 2024)
HIGHLIGHTS Vaginal varicosities are prone to happen in pregnant women with unspecific causes and multifactorial. The mode of delivery in a pregnant woman with vaginal varicosities is still unknown, but it is not an indication of caesarean section. ABSTRACT Objective: Vaginal varicose is a rare condition characterized by dilated veins in the labia majora, labia minora, and vagina. This case report reported a woman with vaginal varicose who experienced labor without any delivery complications. Case Report: The patient, a 29-year-old woman, gravida 3, para 2, presented with discomfort and swelling in the vagina at 32 weeks of gestational age. Despite reaching 39 weeks of gestation, the vaginal varicosities remained stable and painless. She had no prior history of varicose veins, hypertension, blood abnormalities, malignancy, or contraception usage. Physical examination revealed mild varicosities in the labium and significantly swollen varicosities protruding toward the vaginal introitus. Interestingly, a small varicose vein was also noted on her right leg, previously unnoticed by the patient. At 39 weeks pregnant, she experienced spontaneous vaginal delivery without complications. During the third stage of labor, the vaginal varicosities decreased in size, and no rupture occurred. The newborn, a healthy baby boy weighing 2961 grams and measuring 48 cm, was delivered vaginally. Despite a second-degree perineal tear, blood loss was minimal, and no complications nor rupture arose from the varicose veins. Conclusion: Vaginal varicosities are rare, primarily occurring in multigravida pregnant women between 12 and 26 weeks of gestation. This case highlights that cesarean section is not necessarily indicated in pregnant women with vaginal varicosities. The successful vaginal delivery in this instance resulted in no varicose vein rupture, controlled bleeding, and regression of vaginal varicosities postpartum.